2021
DOI: 10.3390/ijerph18063307
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Behavior, Taste Preferences and Special Beer Perception among Romanian University Students: A Qualitative Assessment Research

Abstract: The transition from adolescence to adulthood can be a challenging period for many students. This period is associated with an increase in alcohol consumption (AC) which can develop a drinking behavior or shape the preferences for certain alcoholic beverages. The purpose of this study was to analyze the AC pattern among Romanian university students, by investigating the association between taste and consumption, including preferences for special beer. A 30-item omnibus-type questionnaire was distributed to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…Interestingly, the average age of newcomers drinkers was 16 years; females started drinking alcohol at age ten more quickly than males at age 12. This finding contrasts with results from Romania that males begin to drink faster [13]. This could be the difference in a societal context, including parents' and friends' drinking habits, social normative ideas about alcohol use, and cultural environment influence factors, including attitudes about alcohol consumption.…”
Section: Prevalence Of Alcohol Consumptioncontrasting
confidence: 86%
“…Interestingly, the average age of newcomers drinkers was 16 years; females started drinking alcohol at age ten more quickly than males at age 12. This finding contrasts with results from Romania that males begin to drink faster [13]. This could be the difference in a societal context, including parents' and friends' drinking habits, social normative ideas about alcohol use, and cultural environment influence factors, including attitudes about alcohol consumption.…”
Section: Prevalence Of Alcohol Consumptioncontrasting
confidence: 86%
“…Studies from the literature have shown that both males and females that are binge-drinkers pay less attention in class and are less able to perform specific tasks due to the neurotoxic effect of alcohol on the prefrontal cortex. It is unclear why women have enhanced vulnerability to the neurotoxic effects of alcohol [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that gender influences the habits and preferences of alcoholic consumption, e.g., Jimborean et al (2021) found that Romanian male students drink alcoholic beverages to relax or socialize and, in general, preferred beer, while females consume alcohol for the beverage's taste or flavor and their favorite beverage was wine. In this sense, gender differences between young adults could play a role in the preferred alcoholic beverages (Martínez et al 2017) and could impact the food and beverage pairing preferences of consumers.…”
mentioning
confidence: 99%